Incidence Rate of Positive HBV Discovered in Pre-Operatively Tests at AL-Yarmouk Teaching Hospital during 2020 to 2024 - K. Jameel, Sarab; A. Abdulrazzaq, Russell; K. AL-Taiem, Oruba; H. Mahmood, Israa; H. Hayyawi, Ali; A. Aboud, Aya; S. Hassan, Sura (Journal of Neonatal Surgery, 2025)
ABSTRACT Background: HBV may cause a liver infection that is acute or chronic infection and have a higher prevalence type of hepatitis in developed Countries and in male were more frequently exposed to the risk factors as compared to female. It is a risk factor for hepatocellular carcinoma (HCC), it is commonly transmitted to susceptible individuals especially health workers by several procedures, including transfusion of blood and its products; various surgical procedures; dialysis etc., in addition, some independent factor of age, gender, season and residence could associate with HBV prevalence. Methods: present study was conducted on total (75,702) pre-operative(pre-surgical) blood sample were collected from both genders (38,681 male, 37,021female) with all age groups, were referred to the Department of Teaching Laboratories in AL-Yarmouk Teaching Hospital at Baghdad / Iraq, as a part of procedures of laboratories tests, which covered a period of five years from January2020 to December 2024. The laboratory testing method was Enzyme Linked Immunosorbent Assay (ELISA) BioTek /REF (50TS8) -USA, to detect HBsAg and anti-HBc Ab in serum specimens. Results: from 75,702 total blood samples ,HBV infection was 323(0.4%) patients during 5 study years , 205 males (63.4%) and 118 females (%36.5), the highest rate of HBV infection of pre-operative patients was 95/16307 in 2024 and the age ranged between 10 - 65 years old, when recorded highest percentage of HBV incidence in age group 30-39 (28.7%), also high percentage of HBV infection (r-value = 0.00001) in (Summer and Autumn) seasons (51.3%) when comparable with (Winter & Spring) seasons results (48.6%),furthermore ,there was a significantly relationship (r-value < 0.00001) between positive result of HBV infection 294 (91.0%) and residency in Baghdad which divided to AL-Karkh 280 HBV infection while Al-Rusafa 14 case (86.6% and 4.3%) respectively. Conclusion: The incidence of hepatitis B in Baghdad during the five years of this study was low 323 (0.4%) from75,702 patients, and the incidence of HBV infection was significantly influenced with two factors include: residential areas and seasonal climate (seasons of the year), while the age and gender factors weren’t. It’s necessary to include a screening HBV as laboratory test within the ordinary tests to all patients, to protect the health workers, and confirmation to use the Personal Protective Equipment (PPE) and attempt to improve vaccines programs applied and increased consciousness of the risks and methods of transmission of HBV especially in adolescents and adult’s category.